RAGAM MODEL PEMBELAJARAN DALAM KURIKULUM SD: DARI PENDEKATAN KONVENSIONAL MENUJU PEMBELAJARAN INOVATIF BERBASIS KOMPETENSI - Romi Laspita; Dewi Andini; Muhammad Arif; Atiyah Qonitah; Lili Mulyanti; Raudhatul Hasanah; Syava Firdania; Natasya Az-zahra Nelzira; Nurul Atikah; Rasti Wulandari; Nayla Nabilla; Resya Putri Insani (STKIP Subang, 2026)
Learning models constitute the conceptual framework that determines the direction and quality of the teaching and learning process in the classroom. At the elementary school level, selecting the appropriate learning model is a critical factor in realizing the goals of the Freedom to Learn Curriculum (Kurikulum Merdeka), which is oriented toward the holistic development of the Pancasila Student Profile. This article aims to comprehensively review various learning models relevant to the elementary school curriculum context, encompassing: (1) conventional learning models and their enduring relevance; (2) innovative constructivist-based learning models, including Cooperative Learning, Problem-Based Learning (PBL), and Project-Based Learning (PjBL); and (3) competency-based learning approaches within the Kurikulum Merdeka framework. The study was conducted through systematic literature review of scientific sources from SINTA-accredited journals and educational reference books published between 2006 and 2024. The findings indicate that no single learning model is universally superior across all conditions. Each model possesses distinct theoretical foundations, implementation procedures, strengths, and limitations depending on the learning context. An effective elementary school teacher is one who possesses broad pedagogical literacy capable of reading classroom characteristics and selecting and combining learning models appropriately and adaptively. This article is expected to serve as a useful academic reference for PGSD students and elementary education practitioners in developing their pedagogical competence.